Tear-based aqueous batteries for smart contact lenses enabled by Prussian blue analogue nanocomposites - Yun, Jeonghun (2022)
Batteries for contact lenses fabricated by conventional methods could cause severe damage to the eyes if broken. Herein, we present flexible aqueous batteries that operate in tears and provide a safe power supply to smart contact lenses. Nanocomposite flexible electrodes of carbon nanotubes and Prussian blue analogue nanoparticles for cathode and anode were embedded in UV-polymerized hydrogel as not only a soft contact lens but also an ion-permeable separator. The battery exhibited a discharging capacity of 155 μAh in an aqueous electrolyte of 0.15 M Na-ions and 0.02 M K-ions, equivalent to the ionic concentration of tears. The power supply was enough to operate a low-power static random-access memory. In addition, we verified the mechanical stability, biocompatibility and compatibility with a contact lens cleaning solution. It could ultimately enable a safe power supply for smart contact lenses without risk of injury due to the leakage or breakage of the battery.